Pengaruh Kepuasan Kerja, Motivasi Kerja, dan Beban Kerja Terhadap Kinerja Karyawan Indomaret, dan Alfamart - Jonathan Widarta Wijaya; Antonius Kristian; Patrick Heaven; Steven Virgus Yudistira (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to investigate and evaluate how employee performance at Indomaret and Alfamart is affected by job satisfaction, work motivation, and workload. Although their impact on employee performance is still debated, these elements are essential in fostering a productive workplace. This study used a quantitative methodology, and the population consisted of Alfamart and Indomaret employees. One hundred respondents were sampled, and information was collected using Google Form to distribute the questionnaire. The significant values of 0.741 and 0.269, respectively, which are higher than 0.05, indicating that job happiness and work motivation have no significant impact on employee performance. On the other hand, workload was shown to have a significant impact on employee performance, with a significance value of 0.001—smaller than 0.05. These results suggest that although job happiness and motivation may not directly affect performance, efficient task management can improve employee performance. In short, workload has a significant impact on performance, but job satisfaction and motivation are more important in fostering a positive work atmosphere. While optimizing workload management is recommended, businesses should also consider the importance of fostering an environment that encourages employee engagement and happiness. The small sample size and breadth of the study, which looked at only two businesses, are its main weaknesses. To gain a deeper understanding of employee performance, further research is recommended to increase the number of respondents and include other variables.